Significant Decline of Malaria Incidence in Southwest of Iran (2001–2014) - Shokrollah Salmanzadeh; Masoud Foroutan-Rad; Shahram Khademvatan; Sasan Moogahi; Shahla Bigdeli (Journal of Tropical Medicine)
Iran is considered as one of the malaria endemic countries of the Eastern Mediterranean Region (EMR) and is at risk due to neighboring Afghanistan, Pakistan in the east, and Iraq to the west. Therefore the aim of the present investigation is the evaluation of the trend of malaria distribution during the past decade (2001–2014) in Khuzestan province, southwestern Iran. In this retrospective cross-sectional investigation, blood samples were taken from all malaria suspicious cases who were referred to health centers across Khuzestan province. For each positive subject a questionnaire containing demographic information was filled out. Data analysis was performed using SPSS 18. From a total of 541 malaria confirmed cases, 498 (92.05%) were male and 43 (7.95%) were female. The highest number of infections was seen in 2001 with 161 (29.75%) cases and the lowest was in 2014 with 0 (0%). Also, Plasmodium vivax was identified as dominant species in 478 (88.35%) individuals and P. falciparum comprised 63 (11.65%). The highest infection rate was observed in non-Iranian populations with number 459 (84.85%) and imported cases 508 (93.90%). Also, the majority of subjects were over 15 years of age, 458 (84.65%). Due to proximity to endemic countries which has made the malaria campaign difficult, more effort is needed to control the infection in order to achieve malaria elimination.